INFLUENCE OF MANAGERIAL OWNERSHIP, LEVERAGE, PROFITABILITY, ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Sri Madona Saleh; Elfina Yenti (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
This study aims to see the effect of managerial ownership, leverage, profitability on the disclosure of corporate social responsibility. The type of research used is casual comparative quantitative. The results of this study indicate that managerial ownership has a positive and significant effect on corporate social responsibility. Leverage (DER) has a negative and insignificant effect on corporate social responsibility. Profitability (ROA) has a negative and insignificant effect on corporate social responsibility. Simultaneous testing concludes that managerial ownership, leverage (DER), and profitability (ROA) variables simultaneously have a significant effect on corporate social responsibility. From the coefficient of determination test, it can be concluded that 43.6% of corporate social responsibility disclosures can be explained by managerial ownership, leverage (DER) and profitability (ROA). Keywords:Corporate Social Responsibility, Managerial Ownership, Leverage, And Profitability